2020
DOI: 10.1007/s40520-019-01457-3
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviours, cognitive function, and possible mechanisms in older adults: a systematic review

Abstract: Background: Physical activity can improve cognitive function of older adults, but the influence of sedentary behaviour on cognition is less clear. This systematic review investigated associations between sedentary behaviour and cognitive function in older adults without dementia, and possible mechanisms involved.Methods: Major databases were searched for studies in English between 01/01/1999 and 31/10/2019. The systematic review followed COSMOS-E guideline and a pre-registered protocol (CRD42019122229). Risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
(192 reference statements)
1
34
0
1
Order By: Relevance
“…Hence, our study provides support for the idea that the physical and mental health benefits associated with physical activity also apply in the context a major stressful event (Rebar et al, 2015;Warburton et al, 2006), and thereby confirms that physical activity can play a vital role in coping with stressors. Likewise, our study shows not only the positive effects of low level of sedentary behaviours on individuals' physical and mental health (Boberska et al, 2018;Ekelund et al, 2016;Hamilton et al, 2007;Olanrewaju et al, 2020;Teychenne et al, 2010), but also its role in helping individuals to cope with a major stressful event.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Hence, our study provides support for the idea that the physical and mental health benefits associated with physical activity also apply in the context a major stressful event (Rebar et al, 2015;Warburton et al, 2006), and thereby confirms that physical activity can play a vital role in coping with stressors. Likewise, our study shows not only the positive effects of low level of sedentary behaviours on individuals' physical and mental health (Boberska et al, 2018;Ekelund et al, 2016;Hamilton et al, 2007;Olanrewaju et al, 2020;Teychenne et al, 2010), but also its role in helping individuals to cope with a major stressful event.…”
Section: Discussionsupporting
confidence: 64%
“…As physical activity has been shown to protect both physical and mental health (Rebar et al, 2015;Warburton et al, 2006), it could help people cope with COVID-19 related stress and mitigate its detrimental effects on health. Conversely, sedentary behaviour, defined as any waking behaviour in a reclining, sitting, or lying position that requires an energy expenditure lower than 1.5 Metabolic Equivalent Task (MET) (Sedentary Behaviour Research Network, 2012), has been shown to have a wide range of relatively independent negative health effects, including adverse metabolic conditions, depression, cognitive decline, quality of life and increased mortality (Boberska et al, 2018;Ekelund et al, 2016;Hamilton et al, 2007;Olanrewaju et al, 2020;Teychenne et al, 2010).…”
Section: Introdutionmentioning
confidence: 99%
“…A systematic review of qualitative studies indicated that although older adults understand the health consequences of prolonged SB, they also recognized that some SBs may confer cognitive or social benefits 41 . A systematic review of 18 studies (n = 40 228) concluded that there is still some uncertainty about the relationship between sedentary behavior and cognition in older adults but posited that the underlying mechanisms are likely to be similar to physical activity 42 . There is a need for further research to examine the relationship between different domains of SB and cognitive and mental health in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors agree on the need for further longitudinal studies to determine with more precision the independent effect of different sedentary behaviours on cognitive functions [67][68][69], and to establish the most efficient type of exercise and characteristics of training programmes to counteract cognitive impairment [59,64,70].…”
Section: Discussionmentioning
confidence: 99%